PENINGKATAN KOMPOTENSI GURU MELALUI PELATIHAN MEMBUAT RPP KURIKULUM 2013 DENGAN MENGAKTIFKAN KKG GAH KECAMATAN TEMBUKU KABUPATEN BANGLI TAHUN 2018 - Arnika, Ida Bagus (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The aims of this study is to improve the teacher's potential through training in making lesson plan of curriculum 2013 at the GAH KKG in Tembuku District, and in Bangli Regency. This study is School Action Research (PTS) using two cycles design and each cycle consists of four stages, namely: planning, action, observation, and reflection. A measurement technique in the form of test is used to obtain a quantitative data and an observation sheets is used to obtain a qualitative data. The data was analyzed by using descriptive analysis. The subjects in this study were 30 Hindu Religion Teachers, in GAH KKG with less moderate and capable criteria. The object of this study is the ability of teachers to make a lesson plan of 2013 Curriculum to manage classroom learning. Furthermore, based on the results of this study first, at the end of the first and second cycles there was an increase in the average results of teacher's potential through training. The results of the previous training at 70.00 to 87.60. Then, in the third cycle the professional level of the teacher achieved good grades. Second, it turned out that the increase of teacher's potential through training by activating the GAH KKG in Tembuku district and in Bangli regency in 2018 showed very significant results from the initial conditions before receiving the training.